Um framework para mineração de dados educacionais baseado em serviços web semânticos - Souza, Tarsis Marinho de (2011)
This paper presents a framework for educational data mining based on semantic web services as a solution to the challenges found in this area such as data and methods standardization, educational environments integration and easier to use mining tools for both educators and non-specialist users. The solution also includes a wizard, which aims to facilitate the extension and instantiation of the proposed framework in di erent products. In order to validate the proposed solution, a case study was also performed using data from a real e-learning environment used by students from distance mode courses.